Nomenclature and epitypification of Vriesea (Bromeliaceae) species described in Vellozo’s Flora fluminensis - Kessous, Igor M.; Salgueiro, Fabiano; Costa, Andrea F. (Phytotaxa, 2018)
In the eighteenth century, José Mariano da Conceição Vellozo in his work Flora Fluminensis, sought to expand the floristic knowledge of Rio de Janeiro and surroundings. This was the first flora of Brazil written and edited by a native naturalist. However, the existence and location of the type material of species described in this work are not known. Furthermore, the protologues associated with the plates of some taxa are not descriptive enough. The nomenclatural revision of the two Vriesea species (basionym: Tillandsia) currently accepted, described in Vellozo’s Flora Fluminensis are presented here. Two epitypes, a new synonym and two excluded names are proposed. In addition, a brief taxonomic history, nomenclatural and taxonomic notes are presented.